1999
DOI: 10.1348/000712699161305
|View full text |Cite
|
Sign up to set email alerts
|

Failure to support the right‐shift theory s hypothesis of a ‘heterozygote advantage’ for cognitive abilities

Abstract: Annett's (1985) 'right-shift' theory of language dominance and handedness posits three genotypes, rs++, rs(+)- and rs(-)-, and Annett has hypothesized that there are cognitive ability correlates of these genotypes. The rs++ genotype person is held to be 'at risk' for maldevelopment of spatial or other right hemisphere-based cognitive abilities, and the rs(-)- genotype individual is held to be at risk for maldevelopment of phonological abilities. Noting that there must be some adaptive advantage conferred by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
1
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 13 publications
2
28
1
1
Order By: Relevance
“…Some studies found that left-handers have a lower intellectual performance (Crow, Crow, Done, & Leask, 1998;Hicks & Beveridge, 1978;Lamm & Epstein, 1999;McManus & Mascie-Taylor, 1983;Miller, 1971;Olivier, 1978). However, some studies found no differences between right-and left-handers (Cerone & McKeever, 1999;Gignac & Vernon, 2004;Hardyck, Petrinovich, & Goldmann, 1976;Hicks, 1976;Nettle, 2003;Newcombe & Ratcliff, 1973;Wittenborn, 1946). Finally, some studies found an advantage for left-handers (Annett, 1970;Deutch, 1978;Ehrman & Perelle, 1983;Hicks & Dusek, 1980).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies found that left-handers have a lower intellectual performance (Crow, Crow, Done, & Leask, 1998;Hicks & Beveridge, 1978;Lamm & Epstein, 1999;McManus & Mascie-Taylor, 1983;Miller, 1971;Olivier, 1978). However, some studies found no differences between right-and left-handers (Cerone & McKeever, 1999;Gignac & Vernon, 2004;Hardyck, Petrinovich, & Goldmann, 1976;Hicks, 1976;Nettle, 2003;Newcombe & Ratcliff, 1973;Wittenborn, 1946). Finally, some studies found an advantage for left-handers (Annett, 1970;Deutch, 1978;Ehrman & Perelle, 1983;Hicks & Dusek, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the``right-shift theory'' states that handedness is a by-product of a factor that induces lateralised speech representation in the brain, and that there is over-dominance at this major genetic factor, RS+/± individuals having an overall cognitive advantage over either RS+/ + or RS±/±, due to interference of RS+ and RS± with distinct cognitive functions (Annett, 1985). However, this model has not received strong empirical support (Cerone & McKeever, 1999;McKeever, Cerone, & Chase-Carmichael, 2000). Actually, laterality is likely to have a more complex genetic determinism (Francks, Fisher, MacPhie, Richardson, Marlow, & Stein, 2002;Laval, Dann, Butler, Loftus, Rue, & Leask, 1998).…”
Section: Universite â Montpellier II Francementioning
confidence: 99%
“…We estimated that the participants would have been drawn from a relatively homogeneous background, and consequently possess similar socioeconomic backgrounds and levels of intelligence. The impact of sinistrality upon spatial ability is an ongoing research issue (see Casey 1996;Cerone and McKeever 1999); thus the present sample was limited to dextral participants. From a short questionnaire, participants provided information considered relevant to the study (e.g., handedness, color blindness, gardening experience, specific knowledge of plants).…”
Section: Methodsmentioning
confidence: 99%
“…Annett has proposed that the RS+ allele may favour verbal capacities but heighten the risk of spatial deficits, whereas the 80 BARNETT AND CORBALLIS RS7 allele may enhance spatial and motor skills but increase the risk of verbal deficits. Although she and her colleagues have presented a number of findings consistent with this expectation (e.g., Annett, 1993Annett, , 1999Annett & Kilshaw, 1982;Annett & Manning, 1990), a number of other studies have produced evidence inconsistent with it (e.g., Cerone & McKeever, 1999;McManus, Shergill, & Bryden, 1993;Palmer & Corballis, 1996;Resch et al, 1997).…”
Section: Ambidexterity and Magical Ideation 79mentioning
confidence: 97%